2008
DOI: 10.1016/j.steroids.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biochemical studies of 17-substituted androst-3-enes and 3,4-epoxyandrostanes as aromatase inhibitors

Abstract: A series of 5alpha-androst-3-enes and 3alpha,4alpha-epoxy-5alpha-androstanes were synthesized and tested for their abilities to inhibit aromatase in human placental microsomes. In these series the original C-17 carbonyl group was replaced by hydroxyl, acetyl and hydroxyimine groups. Inhibition kinetic analysis on the most potent steroid of these series revealed that it inhibits the enzyme in a competitive manner (IC(50)=6.5 microM). The achieved data pointed out the importance of the C-17 carbonyl group in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…This finding suggested that the effect of aromatization on injury-induced secondary degeneration may occur by a specific, and perhaps exclusive modulation of apoptotic pathways. In fact, aromatase-dependent inhibition of apoptosis is well established in peripheral organs and in breast cancers [129; 130; 131; 132; 133]. Further, this idea is in excellent agreement with the observed increase in apoptosis in aromatase knockout mice [134] and with more sophisticated measures of apoptosis used in the mammal where E 2 replacement is known to affect Bcl-2 expression [135].…”
Section: Astroglial Aromatization Degeneration and Cytogenesismentioning
confidence: 60%
“…This finding suggested that the effect of aromatization on injury-induced secondary degeneration may occur by a specific, and perhaps exclusive modulation of apoptotic pathways. In fact, aromatase-dependent inhibition of apoptosis is well established in peripheral organs and in breast cancers [129; 130; 131; 132; 133]. Further, this idea is in excellent agreement with the observed increase in apoptosis in aromatase knockout mice [134] and with more sophisticated measures of apoptosis used in the mammal where E 2 replacement is known to affect Bcl-2 expression [135].…”
Section: Astroglial Aromatization Degeneration and Cytogenesismentioning
confidence: 60%
“…For example, the bioactivity of ligand 16 with 6-OH is higher than ligand 18 (without 6-OH). However, esterification or etherification of 4-OH, 6-OH or 19-OH not only reduces the hydrogen bond number, but may also increase the chance of steric bumps, thus, decreases the bioactivity of the ligands (the bioactivity of ligands 13,14,27,28,29,32 are lower than that of ligand 16). Alkyl substituent group at C-4 will increase the steric bumps and thus lower the bioactivity of the ligands.…”
Section: Analysis Of the Optimum Molecular Docking Poses Of Differentmentioning
confidence: 99%
“…Steroidal AIs, such as exemestane and formestane, mimic the natural the substrate of androstenedione and can be converted by the enzyme in reactive intermediates, which bind irreversibly to the aromatase active site, resulting in inactivation of the enzyme [14]. In despite of the success of the third-generation steroidal and nonsteroidal AIs, they still have some major side effects associated with the prolonged clinical use of AIs, such as the onset of resistance in the long-term treatment of the breast cancer and the increase of bone loss [14]. For this reason, it is necessary to search for new potent and specific drugs with lower side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of the C-17 carbonyl group reduces the aromatase inhibition of the corresponding compounds and the data revealed the importance of the C-17 carbonyl group in the D-ring steroids studied for aromatase inhibition activity. [39] To study the effect of extended linear conjugation in ring(s) A and/or B, the effect on the position of the epoxide ring, and the effect of the substituent at the 4-position of a 17-hydroxyimino androstane skeleton structure on aromatase inhibition, Pokhrel et al synthesized 17-hydroxyimino derivatives by adding double bonds at C-1-C-2, at C-4-C-5, at C-6-C-7, or both positions and synthesized 17-hydroxyimino derivatives of 1,2-or 4,5-epoxyandrostene and/ordiene and of 4-substituted 4-androstene. The synthesized 17-hydroxyimino steroidal compounds showed promising aromatase inhibition activity.…”
mentioning
confidence: 99%